The Impact of Board Diversity on Financial Performance: Firm-Level Evidence in Nigeria - Dada, Olawale Bamidele; Gbadebo, Adedeji Daniel; Ibrahim, Majeed Ajibola (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Purpose: The study aims to investigate whether specific dimensions of board diversity enhance firm performance. Method: Panel data from the period of 2015 and 2022, covering 20 listed firms, were analyzed using both OLS and Fixed Effects techniques. Board diversity variables included the proportion of female directors, board members with PhDs, and foreign directors. Control variables included firm age, leverage, asset size, CSR experience, and board size. Two measures of financial performance were used: return on assets (ROA) and return on equity (ROE). Results: The results indicate that the female board has a positive but insignificant effect on ROA and a negative, though also insignificant, effect on ROE. PhD board members show a negative effect on ROA and a weak positive effect on ROE. Foreign board members exhibit mixed effects, positively influencing ROE but negatively associated with ROA, with both insignificant. The Fixed Effects results confirm these patterns, with all board diversity variables showing insignificant impacts. Implications: The findings suggest that while board diversity is a socially valuable governance goal, its financial impact may be limited or context-specific in Nigeria’s industrial and commercial sectors. Regulators and policymakers are encouraged to mandate greater transparency in board composition disclosures, allowing stakeholders to better assess the strategic and symbolic value of board diversity. Novelty: This study contributes to the limited empirical literature on corporate governance in sub-Saharan Africa. It provides robust, model-based evidence on how different dimensions of board composition interact with financial outcomes in the Nigerian context.